The influence of general practitioner and patient sex on the treatment of major depression - Jufresa-Blanch, Elisabeth; Carrilero, Neus; García-Altés, Anna (Frontiers in Pharmacology, 2023)
Biological and sociocultural factors may lead to a significant gender bias in the treatment of major depression, and thus contribute to accentuating gender inequalities. However, the influence of the general practitioner (GP)'s sex on the prescription of antidepressants has not been adequately assessed in previous work and remains unclear today. This retrospective cohort study aims to determine the influence of GP and patient sex on the treatment of major depression. The study population comprised 87,629 patients (33.56% male and 66.44% female) aged over 15 with a new diagnosis of major depression recorded between 2017 and 2019 in Catalonia, Spain.Logistic regression models were used to evaluate the effect of GP sex on therapeutic strategy (i.e., whether antidepressants were prescribed at the first diagnostic visit). Cox proportional hazards models and survival analyses were conducted to compare, according to GP and patient sex, the probability that a patient would be prescribed an antidepressant at any time during the study period. Finally, a multiple linear regression analysis was performed to assess the treatment's pharmacological intensity (monthly fluoxetine-equivalent defined daily dose (DDD)). Female patients were more likely to receive an antidepressant prescription at the time of diagnosis, both by male (OR = 1.11, 95% CI = [1.05, 1.17], p<0.001) and female GPs (OR = 1.13, 95% CI = [1.09, 1.17], p<0.001). Similarly, female patients were 8% and 9% more likely than males to receive an antidepressant prescription from male (HR = 1.08, 95% CI = [1.05, 1.11], p<0.001) and female GPs (HR = 1.09, 95% CI = [0.92, 1.07], p<0.001) respectively during the study period. Female GPs prescribed less than male GPs: an average of 0.39 less monthly fluoxetine-equivalent DDD (β = -0.39, 95% CI = [0.10, -3.92], p<0.001). Few differences are observed between male and female GPs regarding the therapeutic strategy and its intensity for the treatment of major depression. However, both male and female GPs are influenced by biases and stereotypes that 1 Jufresa-Blanch et al.entail differential antidepressant prescribing behaviours in accordance with the sex of the patient and their characteristics.